Preliminary studies on utilization of fruit-waste-compost for cultivation of oyster mushroom (Pleurotus florida (Mont.) Singer) - Yadav, Kaushlesh K; Garg, Neelima; Shukla, P K; Kumar, Sanjay; Yadav, Preeti; Kumar, Devendra (Mushroom Research, 2012)
The present investigation reports a preliminary work on evaluating mango peel and mulberry pomace composts for their suitability to grow oyster mushroom, Pleurotus florida (Mont.) Singer.